2022
DOI: 10.1007/s10554-022-02525-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left atrial appendage orifice following percutaneous left atrial appendage closure using three-dimensional echocardiography

Abstract: Purpose: Percutaneous left atrial appendage (LAA) occlusion is increasingly performed in patients with atrial brillation and long-term contraindications for anticoagulation. Our aim was to evaluate the effects of LAA occlusion with the Watchman device on the geometry of the LAA ori ce and assess its impact on the adjacent left upper pulmonary vein (LUPV) hemodynamics.Methods: We included 50 consecutive patients who underwent percutaneous LAA occlusion with the Watchman device. Three-dimensional images of LAA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Second, the LAA is a very flexible structure. A recent investigation showed that the diameter of the LAA increases by 2 mm after implantation with the Watchman device and the LAA orifice changes from an oval to a more circular shape 20 . Another study found that the compression rate was smaller during follow‐up than during the procedure 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the LAA is a very flexible structure. A recent investigation showed that the diameter of the LAA increases by 2 mm after implantation with the Watchman device and the LAA orifice changes from an oval to a more circular shape 20 . Another study found that the compression rate was smaller during follow‐up than during the procedure 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation showed that the diameter of the LAA increases by 2 mm after implantation with the Watchman device and the LAA orifice changes from an oval to a more circular shape. 20 Another study found that the compression rate was smaller during follow-up than during the procedure. 21 The above studies suggested that the LAA adapts to the shape of the occluder after implantation.…”
Section: Laac In Small Laa: Potential Risk and Feasibilitymentioning
confidence: 99%